2023
DOI: 10.3389/fphar.2023.1182937
|View full text |Cite
|
Sign up to set email alerts
|

Natural products as novel anti-obesity agents: insights into mechanisms of action and potential for therapeutic management

Ummul Fathima Shaik Mohamed Sayed,
Said Moshawih,
Hui Poh Goh
et al.

Abstract: Obesity affects more than 10% of the adult population globally. Despite the introduction of diverse medications aimed at combating fat accumulation and obesity, a significant number of these pharmaceutical interventions are linked to substantial occurrences of severe adverse events, occasionally leading to their withdrawal from the market. Natural products serve as attractive sources for anti-obesity agents as many of them can alter the host metabolic processes and maintain glucose homeostasis via metabolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 299 publications
0
12
0
Order By: Relevance
“…The prevalence of obesity is rapidly increasing worldwide. It is generally accepted that natural products that have been shown to be safe can be used to combat obesity [ 65 ]. A previous in vivo study showed that rats treated with NS oils had a significant decrease in body weight (BW) and a lower risk of developing hyperglycaemia and hyperlipidaemia (serum total cholesterol and triglyceride (TG) levels compared to high-fat-diet (HFD) rats [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of obesity is rapidly increasing worldwide. It is generally accepted that natural products that have been shown to be safe can be used to combat obesity [ 65 ]. A previous in vivo study showed that rats treated with NS oils had a significant decrease in body weight (BW) and a lower risk of developing hyperglycaemia and hyperlipidaemia (serum total cholesterol and triglyceride (TG) levels compared to high-fat-diet (HFD) rats [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absence of side effects makes processed medicinal plants highly sought after, whether pure components or extracts [31]. The diverse characteristics of the moringa tree make it a popular plant for both culinary and medicinal purposes; the tree's pods, leaves, and flowers are all edible [18].…”
Section: Research Discussionmentioning
confidence: 99%
“…Although various antiobesity drugs are currently available, their long-term use can lead to serious side effects [ 34 ]. Thus, studies are necessary to establish a link between the consumption of safe natural food ingredients and a decrease in obesity and related complications [ 35 ]. Research evidence indicates that the consumption of natural products is associated with reduced risk of obesity-related complications [ 36 ].…”
Section: Discussionmentioning
confidence: 99%